Synthesis, spectroscopic characterization, X-ray diffraction studies and in-vitro antibacterial activities of diorganotin(IV) derivatives with N -methyl-4-bromobenzohydroxamic acid - Irshad, Ali; Khan, Naqeebullah; Farina, Yang; Baloch, Nizam; Samiullah, -; Ali, Akbar; Lo, Kong Mun; Murtaza, Ghulam; Attiq-ur-Rehman, - (Elsevier, 2018)
Three new diorganotin(IV) complexes (CH 3 ) 2 Sn(mbbha) 2 (2), (C 4 H 9 ) 2 Sn(mbbha) 2 (3), (C 6 H 5 ) 2 Sn(mbbha) 2 (4), of N-methyl-4-bromobenzohydroxamic acid (Hmbbha) (1) have been synthesized by 2:1 condensation ratio of the parent hydroxamic acid with (CH 3 ) 2 SnO, (C 4 H 9 ) 2 SnO and (C 6 H 5 ) 2 SnO in toluene. Ligand has been synthesized by the reaction of 4-bromobenzoyl chloride and N-methylhydroxylamine hydrochloride. Elemental analysis, IR, multinuclear 1 H, 13 C, 119 Sn NMR spectroscopic techniques have been utilized to investigate the bonding and coordination modes of the ligand and its derivatives. It is found on the basis of spectroscopic and structural investigations that hydroxamate ligand acts as a bidentate chelator and coordinated to tin via carbonyl oxygen and deprotonated hydroxy group. The structures of complexes (3) and (4) have been deduced by X-ray crystallography which reveals octahedral geometry around tin in (C 4 H 9 ) 2 Sn(mbbha) 2 (3) and (C 6 H 5 ) 2 Sn(mbbha) 2 (4) derivatives. The in-vitro antibacterial activities of ligand and its derivatives have been evaluated against one Gram positive and three Gram negative bacterial strains. The derivative (2) has displayed remarkable potency against both Gram positive and Gram negative strains. Anti-pathogenic results have been verified statistically.